2020
DOI: 10.1242/dev.180950
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 10 is a negative regulator of postnatal neurogenesis in the mouse hypothalamus

Abstract: New neurons are generated in the postnatal rodent hypothalamus, with a subset of tanycytes in the third ventricular (3V) wall serving as neural stem/progenitor cells. However, the precise stem cell niche organization, the intermediate steps and the endogenous regulators of postnatal hypothalamic neurogenesis remain elusive. Quantitative lineage-tracing in vivo revealed that conditional deletion of fibroblast growth factor 10 (Fgf10) from Fgf10-expressing β-tanycytes at postnatal days (P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 51 publications
(96 reference statements)
2
33
0
Order By: Relevance
“…While tanycyte-derived newborn neurons may play a role in regulating a range of behaviors ( 3 , 7 , 8 ), levels of postnatal tanycyte-derived neurogenesis are low and virtually undetectable in adulthood ( 9 ). As a result, little is known about the molecular identity or connectivity of tanycyte-derived neurons (TDNs) ( 6 , 9 ). A better understanding of the gene regulatory networks that control neurogenic competence in hypothalamic tanycytes would both give insight into the function of TDNs and potentially identify new therapeutic approaches for modulation and repair of hypothalamic neural circuitry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While tanycyte-derived newborn neurons may play a role in regulating a range of behaviors ( 3 , 7 , 8 ), levels of postnatal tanycyte-derived neurogenesis are low and virtually undetectable in adulthood ( 9 ). As a result, little is known about the molecular identity or connectivity of tanycyte-derived neurons (TDNs) ( 6 , 9 ). A better understanding of the gene regulatory networks that control neurogenic competence in hypothalamic tanycytes would both give insight into the function of TDNs and potentially identify new therapeutic approaches for modulation and repair of hypothalamic neural circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Tanycytes are subdivided into alpha1, alpha2, beta1, and beta2 subtypes based on dorsoventral position and marker gene expression and closely resemble neural progenitors in morphology and gene expression profile. Tanycytes have been reported to generate small numbers of neurons and glia in the postnatal period, although at much lower levels than in more extensively characterized sites of ongoing neurogenesis, such as the subventricular zone of the lateral ventricles or the subgranular zone of the dentate gyrus (3)(4)(5)(6). While tanycytederived newborn neurons may play a role in regulating a range of behaviors (3,7,8), levels of postnatal tanycyte-derived neurogenesis are low and virtually undetectable in adulthood (9).…”
Section: Introductionmentioning
confidence: 99%
“…While tanycyte-derived newborn neurons may play a role in regulating a range of behaviors ( 3 , 7 , 8 ), levels of postnatal tanycyte-derived neurogenesis are low and virtually undetectable in adulthood. Furthermore, little is known about the molecular identity or connectivity of tanycyte-derived neurons ( 6, 9 ). A better understanding of the gene regulatory networks that control neurogenic competence in hypothalamic tanycytes would both give insight into the function of tanycyte-derived neurons and potentially identify new therapeutic approaches for modulation and repair of hypothalamic neural circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Tanycytes are subdivided into alpha1, alpha2, beta1 and beta2 subtypes based on dorso-ventral position, morphology and gene expression profile, and closely resemble neural progenitors in morphology and gene expression profile. Tanycytes have been reported to generate small numbers of neurons and glia in the postnatal period, although at much lower levels than in more extensively characterized sites of ongoing neurogenesis such as the subventricular zone of the lateral ventricles or the subgranular zone of the dentate gyrus (3)(4)(5)(6). While tanycyte-derived newborn neurons may play a role in regulating a range of behaviors (3,7,8), levels of postnatal tanycyte-derived neurogenesis are low and virtually undetectable in adulthood.…”
mentioning
confidence: 99%
“…Although previous studies identified Rax as a tanycyte marker [ [18] , [19] , [20] ], we found that Rax is also expressed in a small population of parenchymal cells. While a subset of these cells had tanycyte-like morphology and probably represents tanycytes that migrated into the parenchyma before differentiation [ 31 , 40 ], the majority represented a different cell type that we termed “frizzy cells”, which were located primarily in the caudal Arc. Rax- negative frizzy cells expressing tdTomato were more broadly distributed, suggesting that frizzy cells move over long distances and downregulate Rax while migrating.…”
Section: Discussionmentioning
confidence: 99%